Statistical Analysis of Data Access Techniques in Cloud - Ashtankar, Nikita; Mulchandani, Mona (International Journal of Computer Sciences and Engineering, 2025)
As per recent trend, cloud computing is the most high in demand, reliable and efficient technology. There are amazing benefits that are available with cloud computing like minimum investment cost, tremendous storage space, virtualization, resource sharing. The Cloud users are beneficial with this technology as they can use the large volume of data in cloud and access it anytime, anywhere easily from any corner of the world. This is achievable in pay per use or pre-paid basis. As this is a pro it also has cons, i.e security and Market competition. Many users can request for data, so, technologist need to ensure they authenticate and authorize the users to access this data. This is achievable thru access control schemes which not only allows a authenticated and authorized user to access the data but also can deny access to malicious user. In this paper we are discussing the same pain area i.e existing access control schemes along with Analysis and techniques to improve the speed of data access.